Identification and Expression of Some Plant Cell Wall-Degrading Enzymes Present in Three Ontogenetics Stages of Thecaphora frezii, a Peanut (Arachis hypogaea L.) Pathogenic Fungus - Soria, Néstor Walter (2022)
Peanuts can be affected by the presence of pathogenic microorganisms. The fungus Thecaphora frezii (T. frezii), which belongs to the taxonomic class Ustilaginomycetes, is the causal agent of the disease known as “peanut smut”. The life cycle of this fungus includes three stages, namely teliospores, basidiospores and hyphae. In the hyphae stage, infection occurs in the peanut plant, which requires the involvement of some enzymes secreted by the fungus. These include the Plant Cell Wall-Degrading Enzymes (PCWDEs), which degrade various polysaccharides. This study aimed to identify the presence of transcript for enzymes belonging to the PCWDEs from three stages of T. frezii. For this, total RNA was extracted from the three ontogenetic stages of T. frezii. These samples were analyzed using an RNA-Seq approach and some transcripts were quantified using Real Time PCR. The analysis of the data provided by the RNA-Seq of the three T. frezii stages, it was possible to identify some transcripts that could encode enzymes compatible with polysaccharides degradation that are part of the plant cell wall. In T. frezii transcriptome, 40 deduced proteins would be enzymes with functions of PCWDEs were identified. They were divided into 27 glycoside hydrolases; two polysaccharide lyases; three carbohydrate esterases and eight enzymes with auxiliary activities. In addition, the fungal SNF1 gene was identified whose activity could be affected by high glucose level, and indirectly influence the levels of some PCWDEs. The analysis of the PCWDEs could help to understand part of the fungal infection process and possibly find substances that can control its development.